The potential of terahertz imaging for cancer diagnosis: A review of investigations to date - Yu, Calvin; Fan, Shuting; Sun, Yiwen; Pickwell-MacPherson, Emma (Quantitative Imaging in Medicine and Surgery, 2012)
The terahertz region lies between the microwave and infrared regions of the electromagnetic spectrum such that it is strongly attenuated by water and very sensitive to water content. Terahertz radiation has very low photon energy and thus it does not pose any ionization hazard for biological tissues. Because of these characteristic properties, there has been an increasing interest in terahertz imaging and spectroscopy for biological applications within the last few years and more and more terahertz spectra are being reported, including spectroscopic studies of cancer. The presence of cancer often causes increased blood supply to affected tissues and a local increase in tissue water content may be observed: this acts as a natural contrast mechanism for terahertz imaging of cancer. Furthermore the structural changes that occur in affected tissues have also been shown to contribute to terahertz image contrast. This paper introduces terahertz technology and provides a short review of recent advances in terahertz imaging and spectroscopy techniques. In particular investigations relating to the potential of terahertz imaging and spectroscopy for cancer diagnosis will be highlighted.